Elicitación de la distribución multinomial a partir de varios expertos (2017)
The objective of this work is to implement an elicitation process to estimate the vector of parameters π to multinomial distribution through of Delphi method. Quantification of opinions and beliefs from multiple experts are used to obtain a single distribution that represents the knowledge of all experts that is a different result to get the sum of individual contributions.